Iterative approach to enantiopure syn/anti-1,3-polyols via proline-catalyzed sequential alpha-aminoxylation and horner-wadsworth-emmons olefination of aldehydes - Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2009)
Iterative use of proline-catalyzed tandem alpha-aminoxylation and HWE olefination of aldehydes provided a simple access to 1,3-polyols. The feasibility of this approach is initially studied to synthesize syn- and anti-1,3-diols and is further extended to a syn/syn-1,3,5-triol at a useful level of asymmetric induction and yield. Its usage is Illustrated by the short synthesis of a hydroxylactone pheromone component, (2S,3S)-2-hydroxyhexylcyclopentanone.